Production of photonic nanojets by using pupil-masked 3D dielectric cuboid; Journal of Physics D: Applied Physics; Vol. 50 - Yue Liyang; Bing Yang; Monks J. N. James; Wang Zengbo; Nguyen Thanh Tung; Vu Dinh Lam; Minin O. V. Oleg Vladilenovich; Minin I. V. Igor Vladilenovich (2017, 2017)
Title screen